Histopathological, immunohistochemical and biochemical evaluation of electroacupuncture treatment of nervus radialis and nervus ulnaris injuries in rabbits - Polat, E.; Gunay, C.; Eroksuz, H.; Yilmaz, S.; Kaya, E.; Karabulut, B.; Incili, C. Akdeniz (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2022)
The aim of this study was to evaluate the efficacy of electroacupuncture in acute and chronic phases of radial and ulnar nerve injuries in histopathological, immunohistochemical and biochemical aspects. In the study, the rabbits were divided into four groups namely acute nerve injury (ANI) group, chronic nerve injury (CNI) group, positive control (PC) group and negative control (NC) group. In the ANI, CNI and PC groups, damage was created on the nervus radialis and nervus ulnaris by applying pressure for 60 seconds using a hemostatic forceps under anesthesia. No damage was created in the NC group. Fifteen sessions of electroacupuncture were applied to the rabbits in the ANI, CNI, and NC groups every other day using LI-4 (Large Intestine Meridian-4, He Gu), LI-10 (Large Intestine Meridian-10, Shou San Li), LR-3 (Liver Meridian-3, Tai Chong), and ST-36 (Stomach Meridian-36, Zusanli) electroacupuncture points. Electroacupuncture was not applied to the rabbits in the PC group. Decapitation was performed under general anesthesia at the end of electroacupuncture applications. After the euthanasia procedure, the samples obtained were evaluated for histopathological, immunohistochemical and biochemical parameters. In conclusion, degenerative foci in the treatment groups were found to be fewer than in the PC group whereas NGF and S-100 immunoreactivity were higher in the treatment groups than in the PC group. Whereas no statistically significant difference was observed between the treatment groups and the NC group in terms of oxidative stress factors, there was a statistically significant difference between the treatment groups and the PC group. In light of all these data, we have concluded that electroacupuncture is an effective treatment method for peripheral nerve injuries.
Keywords: electroacupuncture; histopathological; immunohistochemical; nerve injury; oxidative stress